Telaah Prinsip Kafa’ah dalam Hadis tentang Kriteria Memilih Calon Pasangan (Pendekatan Kaidah al-‘Adatu Muhakkamah) - Maulana, Arif; Saepullah, Usep (Jurnal Penelitian Ilmu Ushuluddin, 2024)
This research aims to examine more deeply the principle of Kafa'ah contained in the hadith regarding choosing a prospective partner who is classified according to four criteria, namely in terms of wealth, ancestry, appearance, and religion. These four criteria are then correlated with the rules of al-'Adatu Muhakkamah because it is considered that there is a tendency for each person to have the habit of choosing a potential partner according to their temperament, in other words choosing someone who is equal or equal to themselves. The research method used is a qualitative method with a library research approach. The results of this research can be concluded that understanding the hadith and opinions of ulama in choosing a mate must be based on the principle of Kafa’ah (equality) where this is also influenced by the habits that exist in society.